Analysis of selected allergic reactions among psoriatic patients - Weryńska-Kalemba, Maria; Filipowska-Grońska, Agata; Kalemba, Michał; Krajewska, Anna; Grzanka, Alicja; Bożek, Andrzej; Jarząb, Jerzy (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Psoriasis is a chronic and recurrent inflammatory skin disease. The aetiology is still unknown in spite of numerous scientific researches. There is very little evidence which does not provide enough knowledge about allergic reactions in psoriatic patients. Based on the fact that the epidermal barrier damage allows different allergen types to penetrate into deep layers of epidermis and skin, we can assume that it may lead to immunological reactions. Aim : To investigate the allergic reaction indicators and hypersensitivity assessment about contact, inhalant and food allergens. The results were analysed with regard to clinical disease indicators and progression stage of dermal lesions. Material and methods: Eighty patients with psoriasis were examined. The concentration of total IgE antibodies and allergen specific IgE antibodies (asIgE) were analysed. Standard epidermal tests and atopy patch tests were performed. All the patients were estimated for their dermatological condition based on the PASI scale. The control group consisted of 50 patients without psoriasis and allergic history. Results : Significantly higher concentration of total E immunoglobulin has been stated in the patients with psoriasis. Higher concentrations of specific allergic IgE antibodies were more often observed in the examined group but the most frequently observed values were present in 1–3 class. The most common airborne allergens were birch, artemisia, timothy and rye pollens. There have not been any significant statistical differences in the case of positive epidermal test results. Conclusions : There is slightly expressed hypersensitivity in psoriatic patients. This hypersensitivity degree correlates with the intensification of symptoms.